Laying rate and egg quality of three hen genotypes in family farming of southwest Algeria - Boubekeur, Abderrahmen; Souddi, Mohammed (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
The quality and number of eggs produced by laying hens introduced into family oasis farms in southwestern Algeria remain poorly studied. This study evaluated the effect of genotype (local hen, Fayoumi, and Plymouth Rock) on egg quality. A total of 180 eggs (60 per genotype) were collected over one year, and their external characteristics (egg weight, length, width, shape index and shell weight) and internal characteristics (yolk weight and albumen weight) were analyzed. A one-way analysis of variance (ANOVA) was used to assess the effect of genotype on the measured egg characteristics. Post hoc comparisons were conducted using Tukey's HSD test. The results showed that genotype had a significant effect on several traits. Egg weight (P<0.05), length (P<0.05), width (P<0.001), shell weight (P<0.001) and albumen weight (P<0.05) differed among genotypes. The shape index also varied (P<0.001), reflecting distinct egg morphology. The external measures were egg weight (Local hen: 44.42 g, Fayoumi: 40.07 g, Plymouth: 46.79 g), length (Local hen: 52.06 mm, Fayoumi: 46.58 mm, Plymouth: 48.80 mm), and width (Local hen: 36.93 mm, Fayoumi: 34.20 mm, Plymouth: 36.58 mm). The internal measures were yolk weight (Local hen: 15.00 g, Fayoumi: 14.37 g, Plymouth: 14.93 g) and albumen weight (Local hen: 24.72 g, Fayoumi: 23.40 g, Plymouth: 27.28 g). In conclusion, the study highlights the importance of considering genetic factors in poultry selection and improvement programs, particularly in family farming systems in southwest Algeria, where improving productivity and egg quality is essential for food security and improving farmers’ livelihoods.